Emotional intelligence (EI) and effective leadership: a case study of a mining company in Zimbabwe - Mahapa, Mildred; Chirasha, Vonai (Midlands State University, 2016)
The study aimed at assessing emotional intelligence as a strategic tool for effective leadership. The research was a case study of a mining company in Zimbabwe. To ensure the aim of the research is achieved 70 people participated in the research, 18 being those in leadership positions and 52 being subordinates without any leadership positions .Face to face interviews were conducted to elicit data from the management. Questionnaires were distributed to all the respondents. The research was based on Goleman s (1998) mixed model of emotional intelligence which looks at self awareness, self management, social awareness and relationship management as factors of emotional intelligence. The major objective of the paper was to assess the relationship between emotional intelligence and effective leadership. Leaders viewed effective leadership style as a combination of the application of both emotional intelligence skills and expertise. Subordinates were of the view that emotional intelligence has greater influence on effective leadership behavior and their performance. The thematic approach was used for data analysis. The research implications are that leaders should be aware of emotional intelligence and learn to separate emotions and real facts.